Murabahah Contract: Implementation on House Ownership Financing Products (KPR) at BNI Syariah Bank KC Palopo - Ines M. Nur; Ahmad Syarief Iskandar; Muhammad Ikram S (Pinisi Business Administration Review, 2020)
ABSTRACTThe purpose of this study was to determine the implementation of the murabahah contract on the financing product of Griya iB Hasanah at PT. Bank BNI Syariah KC Palopo. This type of research is descriptive qualitative by taking a juridical and empirical approach. The research was conducted at the BNI Syariah KC Palopo office. The data in this study were obtained by interview and observation. This study indicates that the implementation of Griya ib Hasanah financing at BNI Syariah Bank uses two models, the first is the murabahah scheme, and the second is the murabahah scheme. The advantage of home financing at Bank BNI Syariah KC Palopo is that it does not impose a fine; if the repayment is made early, there will be no penalty, and the buying and selling process is transparent, there is no element of arrogance. The drawback is that for customers, the process takes quite a long time. Secondly, if market interest rates decline, it will not affect the customer’s installments because, from the beginning of the agreement, it has been agreed that the installments will be fixed starting from the initial installment to the end. However, Islamic banks make an assessment detailed because Islamic banking avoids the risk of uncertainty or traffic jams. So far, the bank is still considered safe because the debtors still have a trustworthy nature, there are no traffic jams, and in the provision of bank financing, BNI Syariah KC Palopo is very careful to avoid all risks that may occur even though the process is long, but avoid everything that may happen vanity.